Budaya Konsumtif Masyarakat Terhadap Minuman Xing Fu Tang di Kota Medan - Syahpitri Surbakti; Rudiansyah Rudiansyah (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
The culture of consuming boba drinks has become a trend and lifestyle of the people, especially in Medan city. The emergence of drinks that are considered interesting to taste and the high consumptive spirit of the community are the reasons. Xing Fu Tang is a type of boba drink originating from Taiwan. The purpose of this study is to find out the reason why Xing Fu Tang is one of the trend drinks for the people of Medan. The object of research is the people who live in Medan city. This study utilizes the theory of Johann Heinrichk Lambert related to phenomenology, in order to find out the deepest nature of the phenomena that occur in everyday life. Using qualitative methods, by utilizing library resources, as well as surveys of 30 people who became the object of study. The findings of this study are that the Xing Fu Tang boba drink has become a trending drink of choice for the community, because of its attractive packaging and well-known brand. The boba texture, distinctive taste and aroma are also the reasons why it is easy to accept and demand. So it was found that the Taiwanese drink culture was able to be accepted by the Indonesian people, especially in Medan city, and even became one of the current trend drink choices.Keyword: xing fu tang; consumer culture; drink; boba; taiwan-indonesia.  ABSTRAKBudaya konsumsi minuman boba telah menjadi tren dan gaya hidup masyarakat, khususnya kota Medan. Munculnya minuman yang dianggap menarik untuk dicicipi dan tingginya jiwa konsumtif masyarakat menjadi alasannya. Xing Fu Tang merupakan salah satu jenis minuman boba yang berasal dari Taiwan. Tujuan penelitian ini untuk mengetahui alasan minuman Xing Fu Tang menjadi salah satu minuman tren masyarakat kota Medan. Objek penelitian adalah kalangan masyarakat yang berdomisili di kota Medan. Penelitian ini memanfaatkan teori dari Johann Heinrichk Lambert terkait fenomenologi, demi mengetahui hakikat terdalam dari fenomena-fenomena yang terjadi dalam kehidupan sehari-hari. Menggunakan metode kualitatif, dengan memanfaatkan sumber pustaka, serta survey terhadap 30 masyarakat yang menjadi objek kajian. Temuan dari penelitian ini yaitu, bahwa minuman boba Xing Fu Tang menjadi pilihan minuman tren masyarakat, sebab kemasannya yang menarik, brend yang telah terkenal. Tekstur boba, rasa dan aroma yang khas juga menjadi alasan mudah diterima dan diminati. Sehingga didapati bahwa budaya minuman Taiwan ini mampu diterima oleh masyarakat Indonesai, khususnya kota Medan, bahkan menjadi salah satu pilihan minuman tren masa kini.Kata Kunci: xing fu tang; budaya konsumtif; minuman; boba; taiwan-indonesia.